Bureaucratic landscapes : interagency cooperation and the preservation of biodiversity - Thomas, Craig W. (Associate professor of political science) (MIT Press, 2003)
Political scientists have long been concerned about the tension between institutional fragmentation and policy coordination in the U.S. bureaucracy. The literature is rife with examples of agencies competing with each other or asserting their independence, while cooperation is relatively rare. This is of particular importance in policy areas such as biodiversity, where species, habitats, and ecosystems cross various agency jurisdictions. Bureaucratic Landscapes explores the reasons for the success and failure of interagency cooperation, focusing on several case studies of efforts to preserve biodiversity in California. The book examines why public officials tried to cooperate and the obstacles they faced, providing indirect evidence of policy impacts as well. Among other topics, it examines the role of courts in prompting agency action, the role of scientific knowledge in organizational learning, and the emergence of new institutions to resolve collective-action problems. Notable findings include the crucial role of environmental lawsuits in prompting agency action and the surprisingly active role of the Bureau of Land Management in resource preservation.
Keywords: Biodiversity conservation -- Government policy -- California -- Case studies.; Biodiversity conservation -- Government policy -- United States -- Case studies.; Natural resources -- California -- Management -- Case studies.; Natural resources -- United States -- Management -- Case studies.; Interorganizational relations -- California -- Case studies.; Interorganizational relations -- United States -- Case studies.; Biodiversity.; Natural resources conservation.; Natural resource management.; California; United States; Biodiversité -- Conservation -- Politique gouvernementale -- Californie -- Études de cas.; Biodiversité -- Conservation -- Politique gouvernementale -- États-Unis -- Études de cas.; Ressources naturelles -- Californie -- Gestion -- Études de cas.; Ressources naturelles -- États-Unis -- Gestion -- Études de cas.; Relations interorganisationnelles -- Californie -- Études de cas.; Relations interorganisationnelles -- États-Unis -- Études de cas.; SCIENCE -- Life Sciences -- Biological Diversity.; NATURE -- Animals -- Wildlife.; Biodiversity conservation -- Government policy; Interorganizational relations; Natural resources -- Management; USA; Biodiversität; Naturschutz; Diversité biologique -- Conservation des ressources -- Politique publique -- États-Unis -- Californie (États-Unis); Relations interorganisationnelles -- États-Unis -- Californie (États-Unis); ENVIRONMENT/Environmental Politics & Policy; Case studies; Case studies.; Études de cas.